True pattern-reversal LED stimulator and its comparison to LCD and CRT displays: visual evoked potential study - Voda, P; Kremláček, J; Kordek, D; Chutná, M; Bezrouk, A (Scientific reports, 2024)
A rapid checkerboard pattern change is used to elicit pattern-reversal visual evoked potentials (PR VEPs). CRT or LCD monitors do not allow immediate reversal of the entire pattern. The study aimed to construct a new stimulator whose characteristics approximate an instantaneous reversal and verify whether the improvement is reflected in PR VEPs. A new stimulator using a matrix of 12 × 48 independent white square LEDs was designed and compared with LCDs and CRTs. The effect on the PR VEP peak times and amplitudes of N70, P100, and P140 waves was evaluated in ten subjects. The LED stimulator showed significantly better performance in the rate of change of illuminance, change of pattern, luminance settling and stability. The PR VEP amplitudes of N75, P100, and N140 did not show significant differences. The sum of interpeak amplitudes was significantly larger for the LCD than for the other monitors. The peak times of the waves evoked by the LED were shorter than those evoked by the LCD and CRT for the N75 wave and a check size of 30 ́. LED stimulators are a better alternative to CRTs for PR VEPs than current LCDs. LEDs also seem to be better than CRTs, but further research is necessary to obtain significant results.